2012
DOI: 10.1523/jneurosci.3221-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Broadening of Inhibitory Tuning Underlies Contrast-Dependent Sharpening of Orientation Selectivity in Mouse Visual Cortex

Abstract: Orientation selectivity (OS) in the visual cortex has been found to be invariant to increases in stimulus contrast, a finding that cannot be accounted for by the original, purely excitatory Hubel and Wiesel model. This property of OS may be important for preserving the quality of perceived stimulus across a range of stimulus intensity. The synaptic mechanisms that can prevent a broadening of OS caused by contrast-dependent strengthening of excitatory inputs to cortical neurons remain unknown. Using in vivo loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 57 publications
8
76
1
Order By: Relevance
“…The increase in gOSI was 25% at 25% contrast, and 15% at 95% contrast. With the visual stimulation alone, orientation tuning was sharper at the higher contrast (gOSI = 0.37 ± 0.12 and 0.46 ± 0.13 at 25% and 95% contrast respectively, p < 0.01, paired t-test, n = 10), consistent with our previous report (Li et al, 2012a). In L4, however, stimulating A1-V1 axons did not have any significant effect on orientation tuning or evoked firing rates (Figure 3K-3R, and Figure S3D-S3E).…”
Section: Resultssupporting
confidence: 92%
“…The increase in gOSI was 25% at 25% contrast, and 15% at 95% contrast. With the visual stimulation alone, orientation tuning was sharper at the higher contrast (gOSI = 0.37 ± 0.12 and 0.46 ± 0.13 at 25% and 95% contrast respectively, p < 0.01, paired t-test, n = 10), consistent with our previous report (Li et al, 2012a). In L4, however, stimulating A1-V1 axons did not have any significant effect on orientation tuning or evoked firing rates (Figure 3K-3R, and Figure S3D-S3E).…”
Section: Resultssupporting
confidence: 92%
“…The laminae were roughly identified based on the density of cell stained with DAPI (4Ј,6Ј-diamidino-2-phenylindole dihydrochloride). The average thickness of the mouse visual cortices was 996 Ϯ 43 m (eight mice), 1053 Ϯ 36 m (eight mice), and 1068 Ϯ 31 m (five mice) at P17-P19, P27-P29, and ϳP60, respectively, and correspondingly the layer 4 was located in the range of about 350 -490, 360 -500, and 360 -500 m. This laminar depth characterization is comparable to findings in previous studies (Li et al, 2012). Fluorescence images were acquired by a Nikon A1R confocal microscope with a 20ϫ objective lens.…”
Section: Methodssupporting
confidence: 87%
“…The construction of highly organized neural circuits requires an activity-dependent refinement of early diffuse synaptic connections after their initial formation (Shatz, 1990;Katz and Shatz, 1996). It has been shown that correlated neuronal activities in the retina (Galli and Maffei, 1988;Meister et al, 1991;Wong et al, 1993), dorsal LGN (Weliky and Katz, 1999), and V1 (Chiu and Weliky, 2002) are critical for instructing the formation of eyespecific segregation of afferent eye inputs at different levels of the visual processing pathway (Stryker and Harris, 1986;Cang et al, 2005;Del Rio and Feller, 2006;Huberman et al, 2006).…”
Section: Correlated Neural Activity In the Developing Visual Systemmentioning
confidence: 99%
See 2 more Smart Citations